Assessing mindfulness-based cognitive therapy intervention for tinnitus using behavioural measures and structural MRI: a pilot study. (2nd December 2019) - Husain, Fatima T.; Zimmerman, Benjamin; Tai, Yihsin; Finnegan, Megan K.; Kay, Emily; Khan, Faaiza; Menard, Christopher; Gobin, Robyn L.
Abstract: Objective: We used a minimally-modified version of Mindfulness-Based Cognitive Therapy (MBCT) to treat symptoms of distress associated with tinnitus. Design: Audiological screening (establishing a baseline) was conducted prior to treatment and at three time-points: pre-intervention, post-intervention and follow-up, 8 weeks after completion of training. MRI tests were also conducted at these three time-points. Study sample: Twenty-one participants were enrolled in the study, of whom 15 completed training and audiological testing and eight completed the MRI portion of the study. Results: Scores on tinnitus-related questionnaires showed a significant decline either from pre- to post-intervention or from pre-intervention to follow-up, despite no significant change during baseline. Voxel-based morphometric analysis of the structural MRI scans revealed clusters in bilateral superior frontal gyrus that exhibited significant increases in grey matter volume over the period of intervention and follow-up. Further, grey matter changes in occipital and cingulate regions correlated with declines in tinnitus handicap. Conclusions: This pilot study supports MBCT as an adequate approach for treating distressing tinnitus and suggests that neuroanatomical changes may reflect reductions in tinnitus-related severity. Although our small sample size precludes drawing strong conclusions, there is potential for assessing neuroanatomical changes due to mindfulness-based interventions in tinnitus.